Experiencing Tchaikovsky: A Listener's Companion - Schroeder, David (Rowman & Littlefield Publishers, 2015)
The music of Tchaikovsky remains as much loved in the twenty-first century as it was a hundred years ago. But it has so much more to offer than luscious orchestration and tuneful melodies. In Experiencing Tchaikovsky: A Listener’s Companion, historian and scholar David Schroeder looks beyond traditional views of Tchaikovsky to explore the dramatic impact of his music by walking readers through the remarkable range of works by this great Russian composer. Drawing on a select, but highly representative, group of compositions from Tchaikovsky’s vast output, from his groundbreaking ballet Swan Lake to his great opera Eugene Onegin, Experiencing Tchaikovsky: A Listener’s Companion offers in-depth explorations without technical jargon. In addition to looking at his ballets and some of his operas, Schroeder probes the many other genres in which Tchaikovsky worked, from his chamber music pieces and symphonies to his other orchestral works and concertos. Throughout, Schroeder draws connections among the works, painting a fuller, more coherent picture of Tchaikovsky through his thematic interests, musical techniques, sonic signatures, and literary and cultural focuses. For context, Schroeder describes the works of personal significance for the composer through such contemporary literature as Tchaikovsky’s letters to Nadezhda von Meck, the wealthy patroness whom he never met. Experiencing Tchaikovsky: A Listener’s Companion is for anyone who left a ballet performance whistling themes from Swan Lake or humming melodies from The Nutcracker. It is the ideal work for concertgoers, music students, opera buffs, ballet enthusiasts, and anyone who appreciates this musical master.